Accountancy of financial management - II, Vol.II: workbook, SYBCom - Ainapure Varsha, Ainapure Mukund (Sheth pub.,Mumbai, 2008)
Commerce
ENGLISH
Keywords: Accountancy of financial management - II, Vol.II: workbook, SYBCom; Commerce; Commerce